2021
DOI: 10.1097/pai.0000000000000972
|View full text |Cite
|
Sign up to set email alerts
|

HMB45/PRAME, a Novel Double Staining for the Diagnosis of Melanocytic Neoplasms: Technical Aspects, Results, and Comparison With Other Commercially Available Staining (PRAME and Melan A/PRAME)

Abstract: PRAME (PReferentially expressed Antigen in MElanoma) is a tumor-associated antigen that was recently found to be expressed by malignant melanocytic lesions but not by benign ones, thus resulting useful in this diagnostic field. PRAME could also be expressed by some normal tissues and nonmelanocytic tumors, suggesting as caution should be adopted to use PRAME as a "pan-melanoma" marker for the differential diagnosis with other malignant tumors. Until now, PRAME expression was exclusively investigated through si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…As neoplastic cells may be scant in a cytological sample, it is important to choose the best ICC markers. PRAME has recently emerged as a novel immunohistochemical marker useful for the differential diagnosis of melanocytic neoplasms [9][10][11]. Lezcano et al have recently demonstrated that up to 94% of CMs show diffuse immunopositivity for PRAME, while benign nevi were negative, or only focally positive [12].…”
Section: Discussionmentioning
confidence: 99%
“…As neoplastic cells may be scant in a cytological sample, it is important to choose the best ICC markers. PRAME has recently emerged as a novel immunohistochemical marker useful for the differential diagnosis of melanocytic neoplasms [9][10][11]. Lezcano et al have recently demonstrated that up to 94% of CMs show diffuse immunopositivity for PRAME, while benign nevi were negative, or only focally positive [12].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, PRAME is expressed in many other tumors (germ cell tumors of the testis, lymphomas, peripheral nerve sheath tumors, ovarian carcinomas, etc.) but not in the majority of desmoplastic cM (one of the most challenging melanocytic lesions), and we already suggested great caution before the adoption of PRAME as a “pan-melanoma” marker [ 96 , 97 , 98 , 99 , 100 , 105 , 106 , 107 ]. We recommend using PRAME in conjunction with DS, adopting a melanocytic marker (HMB-45 or MART-1) only in appropriately selected diagnostic settings and integrating this result with the histologic exam, other immunohistochemical analyses, and molecular techniques in “ really-difficult-to-diagnose ” melanocytic lesions.…”
Section: Diagnosismentioning
confidence: 99%
“…As previously clarified (Chapter 2.2.2. ), our working group has recently developed two DS combining PRAME (nuclear) with HMB-45 and MART-1 (cytoplasmatic) that showed very encouraging results and became part of the immunohistochemical panels routinely used in our laboratory [ 56 , 107 ]. In our experience, these DS (HMB-45/PRAME and MART-1/PRAME) are particularly useful in the following diagnostic scenarios: (1) lesions almost exclusively junctional/intraepithelial (allowing us to not evaluate keratinocytes); (2) lesions with a high inflammatory infiltrate (allowing us to not evaluate lymphocytes); (3) differential diagnosis between NN and MM, especially in SLNB; (4) metastasis of unknown primary tumor and/or primary cutaneous tumor with undifferentiated morphology, especially with limited available histological material.…”
Section: Diagnosismentioning
confidence: 99%
“…3, 4). A single stain for PRAME was additionally performed in all cases of MM-H&N with <76% of PRAME-positive cells (negative according to Lezcano et al16) and the results were superimposable to those observed with double stain for Melan A/PRAME 35. The two incisional biopsies of MM-H&N were both positive only adopting the score of Raghavan et al30 (PRAME-positive cells: 70% and 65%, respectively).…”
Section: Resultsmentioning
confidence: 89%